2009
DOI: 10.1099/jmm.0.007872-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunological analysis and pathological examination of gnotobiotic mice monoassociated with Mycoplasma pneumoniae

Abstract: Although mycoplasmal pneumonia has been generally considered to be a disease with good prognosis, a pathogenic host immune response has been associated with its occurrence. In the present study, the pathogenic significance of the immune response was examined using germfree mice either infected intranasally with Mycoplasma pneumoniae or inoculated with M. pneumoniae antigens (soluble antigen and partially purified antigen). In gnotobiotic mice monoassociated with M. pneumoniae, 10 4 c.f.u. M. pneumoniae per lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Pulmonary injury associated with severe or refractory M. pneumoniae pneumonia may be due to the host's immune response rather than to direct microbial damage. 3,13,16,20,21 Most of the recently published studies have been case reports and the characteristics of RMPP have not been comprehensively expounded.…”
Section: Discussionmentioning
confidence: 98%
“…Pulmonary injury associated with severe or refractory M. pneumoniae pneumonia may be due to the host's immune response rather than to direct microbial damage. 3,13,16,20,21 Most of the recently published studies have been case reports and the characteristics of RMPP have not been comprehensively expounded.…”
Section: Discussionmentioning
confidence: 98%
“…M. pneumoniae soluble antigens were prepared as previously described [20,21]. The cultured bacteria were harvested and washed 5 times by centrifugation at 10000 × g for 20 min ( M. pneumoniae ) or 3000 × g for 15 min ( K. pneumoniae and S. pneumoniae ) in Hanks’ balanced salt solution (Gibco, New York, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that experimental pneumonia can be caused by intranasal inoculation of M. pneumoniae soluble sonicated antigens to specific pathogen-free (SPF) mice [20,21]. In the present study, we prepared a M. pneumoniae antigen induced inflammation model by use of SPF mice recurrently inoculated with M. pneumoniae antigens and performed pathological and immunological analyses to examine the induction mechanisms of Th17 and Treg cells.…”
Section: Introductionmentioning
confidence: 97%
“…Serum ferritin levels are generally high in cases of hemophagocytic syndrome with hypercytokinemia [12]. In addition, the patient's extraordinarily high M. pneumoniae titer levels could be related to the degree of virulence [13]. Although methylprednisolone pulse therapy is an effective treatment for hemophagocytic syndrome due to severe M. pneumoniae pneumonia [1], we gave our patient prednisolone 2 mg/kg/ day and macrolides (or minocycline).…”
Section: Discussionmentioning
confidence: 96%